Uji aktivitas antioksidan ekstrak etanol daun bunga melati (Jasminum sambac (L.) Sol. ex Aiton) dengan metode DPPH - Selfiani Selfiani; M. Pandapotan Nasution; Anny Sartika. D; Yayuk Putri Rahayu (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Antioxidant compounds are substances that can absorb or neutralize free molecules so they can prevent degenerative diseases such as heart disease and cancer. Antioxidants are able to donate electrons to stop free radical chain reactions that can damage the body. Jasmine flower leaves contain bioactive substances such as flavonoids, alkaloids, and tannins which are potential ingredients as natural antioxidants. One method to measure or determine free radical scavenging antioxidants is the DPPH (1,1-Diphenyl-2-Picrylhidrazyl) method. This study aims to determine the antioxidant activity of the ethanol extract of jasmine leaves based on the IC value50. The methods used in this study included examination of simplicia characteristics, phytochemical screening and antioxidant activity tests using the DPPH method (1,1-Diphenyl-2-picrylhidrazyl) using a UV-Vis spectrophotometer. The results of this study revealed that the ethanol extract of jasmine flower leaves (Jasminum sambac (L.) Sol. ex Aiton) showed that the extract contained chemical compounds of alkaloids, flavonoids, saponins, tannins, and steroids. In addition, this study also revealed that the ethanol extract of jasmine leaves has antioxidant activity with an IC value50 namely 56.05 µg/mL and for vitamin C the IC value was obtained50 3.70 µg/mL. This shows that the ethanol extract of jasmine leaves positively contains secondary metabolites and has the potential as an antioxidant with a strong classification compared to vitamin C, which is an antioxidant with a very strong classification.